Peptide-independent Recognition by Alloreactive Cytotoxic T Lymphocytes (CTL) - Smith, Pamela A. (The Rockefeller University Press, 1997)
We have isolated several H-2K(b)–alloreactive cytotoxic T cell clones and analyzed their reactivity for several forms of H-2K(b). These cytotoxic T lymphocytes (CTL) were elicited by priming with a skin graft followed by in vitro stimulation using stimulator cells that express an H-2K(b) molecule unable to bind CD8. In contrast to most alloreactive T cells, these CTL were able to recognize H-2K(b) on the surface of the antigen processing defective cell lines RMA-S and T2. Furthermore, this reactivity was not increased by the addition of an extract containing peptides from C57BL/6 (H-2(b)) spleen cells, nor was the reactivity decreased by treating the target cells with acid to remove peptides bound to MHC molecules. The CTL were also capable of recognizing targets expressing the mutant H-2K(bm8) molecule. These findings suggested that the clones recognized determinants on H-2K(b) that were independent of peptide. Further evidence for this hypothesis was provided by experiments in which H-2K(b) produced in Drosophila melanogaster cells and immobilized on the surface of a tissue culture plate was able to stimulate hybridomas derived from these alloreactive T cells. Precursor frequency analysis demonstrated that skin graft priming, whether with skin expressing the wild-type or the mutant H-2K(b) molecule, is a strong stimulus to elicit peptide-independent CTL. Moreover, reconstitution experiments demonstrated that the peptide-independent CTL clones were capable of mediating rapid and complete rejection of H-2–incompatible skin grafts. These findings provide evidence that not all allorecognition is peptide dependent.